2021
DOI: 10.3390/diagnostics11091693
|View full text |Cite
|
Sign up to set email alerts
|

Focal Parenchymal Atrophy of the Pancreas Is Frequently Observed on Pre-Diagnostic Computed Tomography in Patients with Pancreatic Cancer: A Case-Control Study

Abstract: Pancreatic ductal adenocarcinoma (PDAC) accounts for the majority of all pancreatic cancers and is highly lethal. Focal parenchymal atrophy (FPA) of the pancreas has been reported as a characteristic imaging finding of early PDAC. Here, we reviewed 76 patients with PDAC who underwent computed tomography (CT) between 6 months and 3 years before PDAC diagnosis, as well as 76 sex- and age-matched controls without PDAC on CT examinations separated by at least 5 years. FPA was observed corresponding to the location… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 37 publications
3
17
0
Order By: Relevance
“…This finding is expected, as this finding is secondary to the PC-associated obstructive pancreatitis. A recent study showed that pancreatic atrophy was present in approximately 34% of patients with PC, as even the authors suggested that pancreatic atrophy might be an early sign of the development of PC [18]. In our study, we did not have data regarding the presence of pancreatic atrophy prior to the diagnosis of PC.…”
Section: Discussionmentioning
confidence: 60%
“…This finding is expected, as this finding is secondary to the PC-associated obstructive pancreatitis. A recent study showed that pancreatic atrophy was present in approximately 34% of patients with PC, as even the authors suggested that pancreatic atrophy might be an early sign of the development of PC [18]. In our study, we did not have data regarding the presence of pancreatic atrophy prior to the diagnosis of PC.…”
Section: Discussionmentioning
confidence: 60%
“…Recently, several reports have found a relationship between FPA and early pancreatic cancer 8–11 . FPA is thought to arise from low‐grade pancreatic intraepithelial neoplasm (PanIN) the pre‐cancerous stage of PDAC 12 .…”
Section: Discussionmentioning
confidence: 99%
“…In a multicenter study of early stage PDAC in Japan, MPD dilatation could be detected in approximately three-quarters of the Stage 0 cases (76.5% cases on US, 72.0% on CT, and 73.9% on MRI), whereas pancreatic tumors could only be detected in approximately 10% of cases (8.8% cases on US, 10.0% on CT, and 10.9% on MRI) 12 . In addition to MPD abnormalities, recent studies have shown that focal parenchymal atrophy of the pancreas on CT serves as an important imaging sign for the early diagnosis of PDAC 38 , 39 . Of note, Miura et al 39 reported that focal parenchymal atrophy might be the earliest sign of PDAC, which appears before MPD abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to MPD abnormalities, recent studies have shown that focal parenchymal atrophy of the pancreas on CT serves as an important imaging sign for the early diagnosis of PDAC 38 , 39 . Of note, Miura et al 39 reported that focal parenchymal atrophy might be the earliest sign of PDAC, which appears before MPD abnormalities. Novel biomarkers, such as non-coding RNAs, exosomes, and circulating DNA, have been reported to improve the accuracy of diagnosis 40 42 .…”
Section: Discussionmentioning
confidence: 99%